Spotlight on Lonapegsomatropin Once-Weekly Injection and Its Potential in the Treatment of Growth Hormone Deficiency in Pediatric Patients - Miller BS; Yuen KCJ (Dove Medical Press, 2022)
Bradley S Miller,1 Kevin CJ Yuen2 1Pediatric Endocrinology, University of Minnesota Medical School, Minneapolis, MN, USA; 2Department of Neuroendocrinology and Neurology, Barrow Pituitary Center, University of Arizona College of Medicine and Creighton School of Medicine, Phoenix, AZ, USACorrespondence: Bradley S Miller, Division of Endocrinology, Department of Pediatrics, University of Minnesota Masonic Children's Hospital, 201 Academic Office Building, 2450 Riverside Avenue S, Minneapolis, MN, 55014, USA, Tel +1 612 624 5409, Fax +1 612 626 5262, Email mille685@umn.eduAbstract: Lonapegsomatropin, a long-acting GH therapy (LAGH), was approved by the United States Food and Drug Administration in August 2021 for the treatment of pediatric growth hormone deficiency (GHD). Lonapegsomatropin is a prodrug consisting of unmodified GH transiently conjugated to methoxypolyethylene glycol which enables time-release of GH with a half-life of ∼ 25 hours allowing for once-weekly administration. Clinical trials of lonapegsomatropin have demonstrated positive efficacy results in children (phase 2 and 3) and adults (phase 2) with GHD. The phase 3 trial in children with GHD established non-inferiority and statistical superiority of height velocity with lonapegsomatropin (11.2 cm/yr) compared to daily GH (10.3 cm/yr), with no concerning side effects with lonapegsomatropin. Similar growth responses have been reported in other LAGH products in phase 2 (somapacitan) and phase 3 (somatrogon) trials. Lonapegsomatropin is distributed in temperature-stable, prefilled cartridges at 9 different doses that can be prescribed based upon specific weight brackets designed to deliver approximately 0.24 mg/kg/wk. An electronic delivery device is required to combine the powdered medication with the diluent and deliver the medication subcutaneously through a small gauge needle to the recipient. The pharmacodynamic data from the clinical trials of lonapegsomatropin has been used to develop models to estimate an average IGF-1 value drawn at any time during the weekly injection interval. This average IGF-1 value may be used to for safety monitoring and/or to guide dose adjustment. New LAGH products, including lonapegsomatropin, may potentially improve patient adherence, quality of life and clinical outcomes, particularly in patients with poor adherence to daily GH injections in the future. With the availability of new LAGH products, clinicians will need to identify the best candidates for LAGH therapy and understand how to monitor and adjust therapy. Long-term surveillance studies are needed to demonstrate adherence, efficacy, cost-effectiveness and safety of LAGH preparations.Keywords: growth, long-acting growth hormone, IGF-1, growth hormone deficiency, pediatric, adult